Growing up wild : bears - Markle, Sandra (New York, N.Y. : Scholastic Inc., 2000)
Describes different kinds of bear cubs and the changes they go through in their appearance and behavior as they grow up and become successful adult bears.
G8
Keywords: Bears -- Infancy -- Juvenile literature; Bears; Animals -- Infancy